Did Artapanus Use the Septuagint? - Hitchcock, Jason D. (2020)
Many contend that the Hellenistic-era author Artapanus employed the LXX translation, albeit in relatively liberal fashion. Departures from LXX narratives are attributed to his literary and apologetic interests. Although he may have relied upon a combination of oral and written sources, most scholars presuppose his primary reliance upon the LXX. This paper evaluates arguments for Artapanus's use of the LXX, highlighting the paucity of decisive verbal links and weakness of other proposed linguistic correspondences, and attributing the emergence of similar Greek naming conventions between Artapanus and the LXX to the shared Egyptian provenance. These findings challenge the prevailing consensus concerning Artapanus's source for Jewish traditions.
Keywords: Artapanus; Exodus; LXX; Names; Translation